Pengembangan Inovasi Produk Olahan Kentang untuk Meningkatkan Nilai Ekonomi Agribisnis - Pitri Damayanti Tanjung; Greace Masrouli Malau; Zizi Zalianty; Aenisyah Larasati Putri Gultom; Putri Ananda; Lokot Muda Harahap (Jurnal Ekonomi Pertanian dan Agribisnis, 2026)
Potatoes are one of the horticultural commodities that have high economic value and increasing demand. Processing potatoes into innovative products can increase added value, extend shelf life, and create new business opportunities. This study aims to analyze the development of potato-based product innovation in increasing agribusiness economic value.The method used in this research is a literature study by reviewing scientific journals, books, and relevant publications. The results show that product innovations such as potato chips, french fries, croquettes, and frozen potato products significantly increase product value compared to raw potatoes. In addition, innovation improves competitiveness, expands market opportunities, and increases income for agribusiness actors.